Activity of Lipase and Chitinase Immobilized on Superparamagnetic Particles in a Rotational Magnetic Field - Mizuki, Toru (Public Library of Science, 2013)
We immobilize hydrolases such as lipase and chitinase on superparamagnetic particles, which are subjected to a rotational magnetic field, and measure the activities of the enzymes. We find that the activities of lipase and chitinase increase in the rotational magnetic field compared to those in the absence of a magnetic field and reach maximum at certain frequencies. The present methodology may well be utilized for the design and development of efficient micro reactors and micro total analysis systems (μ-TASs).